Association between road accidents and low-grade hepatic encephalopathy among Sri Lankan drivers with cirrhosis: a prospective case control study. (December 2016) - Subasinghe, S.; Nandamuni, Y.; Ranasinghe, S.; Niriella, M.; Miththinda, J.; Dassanayake, A.; Silva, A.; Silva, H.
Abstract Background Low-grade hepatic encephalopathy (LGHE) comprises minimal hepatic encephalopathy (MHE) and grade 1 hepatic encephalopathy. LGHE has no or minimal recognizable symptoms but has mild cognitive and psychomotor deficits. Studies in Western countries have demonstrated increased road accidents (RA) among patients with MHE. Our objective was to investigate the association between Sri Lankan LGHE phenotype and RA. Study design and methods A prospective, case–control study was conducted in the University Medical Unit, North Colombo Teaching Hospital, Ragama Sri Lanka. Patients with cirrhosis of any aetiology, without OHE, who had been driving during previous 1 month were included. A similar number of age matched, healthy control drivers were also enrolled. Both groups were subjected to five pencil-paper based psychometric tests used to detect LGHE in cirrhotics. Self-reported RA during the previous 1 month were recorded: categorized as 'major' when resulted in hospitalization of the involved, 'minor' when there were injuries, but not serious enough for hospitalization of the involved and 'other' when limited to damages to vehicle or environment without injuries. Results Among 55 drivers with cirrhosis and LGHE [males, median age 53 years (range 30–60)], 7 (12.7 %) reported RA compared to 6 (10.9 %) among 55 controls [males; median age 51 years (range 30–60)]. There were no 'major' accidents in either group. 2/55 (3.6 %) cases and 2/55 (3.6 %) controls reported 'minor' accidents. Conclusion There was no increased frequency of RA among Sri Lankan drivers with LGHE compared to healthy controls. This is with the limitation of the study based only on self reported RA.